Was ist ein Ghetto? Konstruktion eines soziologischen Konzepts - Wacquant, Loïc (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2004)
Altbough the social sciences have made extensive use of the term "ghetto" as a descriptive term, they have failed to forge a robust analytical concept of the same. This article constructs a relational concept of the ghetto as a Janus-faced instrument of ethnoracial closure and control. A ghetto is an social-organizational device composed of four elements (stigma, constraint, spatial confinement, and institutional encasement) that employs space to reconcile the two antinomic purposes of economic exploitation and social ostracization.